Analysis of the Quality of Life of the Elderly in the Village of Bukit Harapan - Aszrul AB; Andi Suswani; Buharman (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Quality of life is a person's perception in a cultural context and norms that are relevant to the person's place of life-related to the goals, expectations, standards, and concern for his life. The purpose of this study was to determine the quality of life of the elderly in terms of physical, psychological, level of independence, social, environmental, spiritual life in Bukit Harapan Village in 2018. This study uses a descriptive survey method with a